ARE THE PUBLIC ORGANIZATIONS OBLIGED TO PAY THE VEHICLE EQUITY TAX ON THE OWNERSHIP OF THEIR VEHICLES? - Arteaga Cruz, Stephanie Lauren (2019)
The article it will be absolved regarding whether or not public bodies are obliged to pay taxes on the concept of the Vehicle Equity Tax, from the definition of a tax and its direct relationship with the principle of contributory capacity; as well as, if they are included within the unaffectedness referred to in article 37 of the Single Ordered Text of the Municipal Taxation Law. In the same way, if the pronouncements issued by the Fiscal Court and by the Supreme Court of Justice of the Republic, on the matter, are subject to the nature of the tax and the principle defined above.